2015
DOI: 10.3109/10408444.2014.973934
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicogenomics and traditional approaches to inform mode of action and points of departure in human health risk assessment of benzo[a]pyrene in drinking water

Abstract: Toxicogenomics is proposed to be a useful tool in human health risk assessment. However, a systematic comparison of traditional risk assessment approaches with those applying toxicogenomics has never been done. We conducted a case study to evaluate the utility of toxicogenomics in the risk assessment of benzo[a]pyrene (BaP), a well-studied carcinogen, for drinking water exposures. Our study was intended to compare methodologies, not to evaluate drinking water safety. We compared traditional (RA1), genomics-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 221 publications
(321 reference statements)
2
102
1
Order By: Relevance
“…Neurotoxic effects were observed following oral administration of as little as 0.02 mg/ kg-bw-day (Table 3; e.g., [12]), a LOAEL that is lower than all of the toxic endpoints reviewed by the Cal/EPA (2010). Indeed, our detailed review of BaP-associated effects revealed that neurotoxic endpoints showed the lowest NOAELs overall [13]. These data suggest that BaP neurotoxicity warrants careful consideration for human health risk assessment purposes.…”
Section: Introductionmentioning
confidence: 93%
“…Neurotoxic effects were observed following oral administration of as little as 0.02 mg/ kg-bw-day (Table 3; e.g., [12]), a LOAEL that is lower than all of the toxic endpoints reviewed by the Cal/EPA (2010). Indeed, our detailed review of BaP-associated effects revealed that neurotoxic endpoints showed the lowest NOAELs overall [13]. These data suggest that BaP neurotoxicity warrants careful consideration for human health risk assessment purposes.…”
Section: Introductionmentioning
confidence: 93%
“…The mechanisms of BaP mutagenicity have been well characterized and reviewed for somatic tissues1821. The primary mechanism is the faulty replication of unrepaired DNA adducts formed by a BaP metabolite, benzo( a )pyrene-7,8-dihydrodiol-9,10-epoxide (BPDE).…”
mentioning
confidence: 99%
“…Epidemiological and experimental animal studies associate exposure to BaP with an increased risk of several forms of cancer, including tumors in the forestomach, oral cavity, liver, and lung (Moffat et al, 2015). Furthermore, we can detect NPAHs, such as 1-nitropyrene, 3-nitrobenzanthrone, and 6-nitrochrysene, in samples from the Alexandria and Suez Canal sites.…”
Section: Discussionmentioning
confidence: 76%
“…Benzo[a]pyrene (BaP) is a kind of PAH well known as a toxic substance and carcinogen (Kizu et al, 2003;Moffat et al, 2015). Epidemiological and experimental animal studies associate exposure to BaP with an increased risk of several forms of cancer, including tumors in the forestomach, oral cavity, liver, and lung (Moffat et al, 2015).…”
Section: Discussionmentioning
confidence: 99%